THE CHALLENGES OF IDEALS WOMANHOOD IN THE LODGER NOVEL BY MARIE BELLOC LOWNDES - Tria Nur Hidayah (Fakultas Ilmu Budaya Universitas Mulawarman, 2021)
This study is focused on the challenges of the ideals womanhood in Victorian era in Ellen’s character. Ellen is one of the main characters in the The Lodger novel. The novel was inspired by Jack the Ripper killings that was set in Victorian period. This novel tells the story of a serial killer terrorizing the capital. This novel is focused on one of the lives of the London family who are trying to survive in economic difficulties. This research used The Lodger novel as the data source and for the data the researcher used the narration and dialogue that contained the challenges of the ideals womanhood in Victorian era. By using mimetic approach, the research aimed to answer the following question. The research question is how the main character challenges the ideals womanhood through her roles in the The Lodger Novel. The result of the analysis using the ideals of womanhood in Victorian Britain by Lynn Abrams theory, the researcher found seven ideals challenged by Ellen Bunting, they are; 1) the icon, 2) the ideal woman, 3) at home, 4) household management, 5) the ideology, 6) wife and mother, and 7) social responsibility.